Innocence and the Guilty Mind - Smith, Stephen F. (2018)
For decades, the “guilty mind” requirement in federal criminal law has been understood as precluding punishment for “morally blameless” (or “innocent”) conduct, the goal being to define the mental element in terms that will protect offenders from conviction unless they had adequate notice of the wrongfulness of their conduct. The Supreme Court’s recent decision in Elonis v. United States signals a significant shift in mens readoctrine, recognizing for the first time the potential for disproportionately severe punishment as a justification for heightened mens rea requirements. This long-overdue doctrinal move makes perfect sense because punishment without culpability and excessive punishment involve the same objectionable feature: the imposition of morally undeserved punishment. This Article uses Elonis as a vehicle for re-examining the effectiveness of current mens rea doctrine. In addition to the unjustified absence of proportionality considerations as a recognized factor in mens reaselection before Elonis, mens rea doctrine is hobbled by several methodological flaws, flaws traceable to the doctrine’s simultaneous embrace of two irreconcilable views of the separation of powers in criminal law. The project of reading implied mens rea requirements into statutes necessarily assumes that courts have a lawmaking role on par with Congress in fleshing out incomplete legislative crime definition, but the mens reaselection methodology reflects standard faithful-agent textualism. This turns out to be the doctrine’s Achilles heel because punishment without culpability stems primarily from poor legislative crime definition. To be truly effective, mens rea doctrine must operate outside the statutory definition of the offense, with all mens rea options – even knowledge of criminality – being available wherever needed to prevent morally undeserved punishment. Otherwise, mens rea doctrine will fail to deliver on its central, and vitally important, promise of preventing conviction for morally blameless conduct